THE REALIZATION OF ATTITUDE ANALYSIS ON MALE AND FEMALE SECOND-YEAR STUDENTS’ NARRATIVE TEXTS - Vivi Putriyantina; Iskhak Said (JALL (Journal of Applied Linguistics and Literacy), 2018)
This study was aimed to find out the realization of attitude analysis in the students narrative texts. The writers applied qualitative design particularly descriptive qualitative as the method. The results asserted 421 clauses realized on male and female second-year students’ narrative texts. There were150 attitudes which consisted of 51 attitudes on male narrative texts and 99 attitudes on female narrative texts. Meanwhile, those covered 76 affects, 24 judgements, and 50 appreciations realized on male and female second-year students narrative texts. From those aspects, the most dominant aspect was realized by affect. In conclusion, the realization of attitude analysis on male and female second-year students’ narrative texts was realized 150 items, which were dominated by 76 items (51%) realization of affect. Finally, it is expected that through learning attitude, the students can improve their writing skill and choose the proper vocabularies in composing English text. Besides, it is suggested for further researchers to enrich their research by conducting research with the full-package of appraisal system which cover affect, engagement, and graduation. Keywords: SFL; Interpersonal meaning; Appraisal System